Small heat shock protein Hsp67Bc plays a significant role in Drosophila melanogaster cold stress tolerance. - Malkeyeva, D.; Kiseleva, E.; Fedorova, S. (Journal of Experimental Biology, 2020)
Hsp67Bc in Drosophila melanogaster is a member of the small heat shock protein family, the main function of which is to prevent the aggregation of misfolded or damaged proteins. Hsp67Bc interacts with Starvin and Hsp23, which are known to be a part of the cold stress response in the fly during the recovery phase. In this study, we investigated the role of the Hsp67Bc gene in the cold stress response. We showed that in adult Drosophila, Hsp67Bc expression increases after cold stress and decreases after 1.5 h of recovery, indicating the involvement of Hsp67Bc in short-term stress recovery. We also implemented a deletion in the D. melanogaster Hsp67Bc gene using imprecise excision of a P-element, and analysed the cold tolerance of Hsp67Bc-null mutants at different developmental stages. We found that Hsp67Bc-null homozygous flies are viable and fertile but display varying cold stress tolerance throughout the stages of ontogenesis: the survival after cold stress is slightly impaired in late third instar larvae, unaffected in pupae, and notably affected in adult females. Moreover, the recovery from chill coma is delayed in Hsp67Bc-null adults of both sexes. In addition, the deletion in the Hsp67Bc gene caused more prominent up-regulation of Hsp70 following cold stress, suggesting the involvement of Hsp70 in compensation of the lack of the Hsp67Bc protein. Taken together, our results suggest that Hsp67Bc is involved in the recovery of flies from a comatose state and contributes to the protection of the fruit fly from cold stress.